Concussion management in US college football: progress and pitfalls. (March 2016) - Baugh, Christine M; Kroshus, Emily
Reducing the frequency and severity of concussions from sport is an important issue in public health currently addressed by a multifaceted approach. Given the large number of participants and the comparatively high risk of injury, American football is an important sport to consider when examining concussion management practices. Focusing on American football at the collegiate level, this manuscript describes current research regarding concussion epidemiology, policy, implementation of clinical diagnosis, management and return-to-play standards and athlete concussion education. Although American collegiate sports leagues have put forth concussion-related policies in recent years, the implementation of these policies and related effects on athlete concussion education, clinical management of concussion and ultimately athlete health outcomes are not well understood. Additional research is needed.